(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper undertakes a comprehensive investigation into the pivotal role of digital activism within Nigeria’s democratic framework, specifically its influence on public and civic engagement. The advent of social media networks has emerged as a significant tool for disseminating information and mobilizing support for various causes. Drawing upon the theoretical lens of technological determinism, this study critically examines the intricate relationship between digital activism and political participation in Nigeria since the return of democratic governance in 1999. Employing a descriptive research design complemented by a qualitative review of existing literature, the findings reveal that digital activism, if not properly organized, can yield adverse outcomes. Consequently, the paper advocates for a holistic approach to managing digital activism, emphasizing effective collaboration between those spearheading progressive causes and the government. By analyzing the multifaceted impacts of digital activism, this research contributes to a deeper understanding of its complexities and significance within Nigeria’s political landscape.